Optimal PLA+ 3D Printing Parameters through Charpy Impact Testing: A Response Surface Methodology - Engelbert Harsandi Erik Suryadarma; Pringgo Widyo Laksono; Ilham Priadythama (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2024)
Additive manufacturing (AM) has revolutionized the manufacturing sector, particularly with the advent of 3D printing technology, which allows for the creation of customized, cost-effective, and waste-free products. However, concerns about the strength and reliability of 3D-printed products persist. This study focuses on the impact of three crucial variables—infill density, printing speed, and infill pattern—on the strength of PLA+ 3D-printed products. Our goal is to optimize these parameters to enhance product strength without compromising efficiency. We employed Charpy impact testing and Response Surface Methodology (RSM) to analyze the effects of these variables in combination. Charpy impact testing provides a measure of material toughness, while RSM allows for the optimization of multiple interacting factors. Our experimental design included varying the infill density from low to high values, adjusting printing speeds from 70mm/s to 100mm/s, and using different infill patterns such as cubic and others. Our results show that increasing infill density significantly boosts product strength but also requires more material and longer processing times. Notably, we found that when the infill density exceeds 50%, the printing speed can be increased to 100mm/s without a notable reduction in strength, offering a balance between durability and production efficiency. Additionally, specific infill patterns like cubic provided better strength outcomes compared to others. These findings provide valuable insights for developing stronger and more efficient 3D-printed products using PLA+ materials. By optimizing these parameters, manufacturers can produce high-strength items more efficiently, thereby advancing the capabilities and applications of 3D printing technology in various industries.